Centuries of compounding human influence on Amazonian forests - Crystal N. H. McMichael; Mark B. Bush; Hans ter Steege; Dolores R. Piperno; William D. Gosling; Majoi N. Nascimento; Umberto Lombardo; Luiz de Souza Coelho; Iêda Leão do Amaral; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Carolina V. Castilho; et al. (Proceedings of the National Academy of Sciences, 2025)
Recent evidence suggests that the ecological footprints of pre-Columbian Indigenous peoples in Amazonia persist in modern forests. Ecological impacts resulting from European colonization c. 1550 CE and the Amazonian Rubber Boom c. 1850 to 1920 CE are largely unexplored but could be important additive influences on forest structure and tree species composition. Using environmental niche models, we show the highest probabilities of pre-Columbian and colonial occupation sites, and hence human-induced ecological influences, occurred in forests along rivers. In many areas, the predicted pre-Columbian and colonial distributions overlap spatially with the potential for superimposed ecological influences. Environmental gradients are known to structure Amazonian vegetation composition, but they are also strong predictors of past human influence, both spatially and temporally. Our comparisons of model outputs with relative abundances of Amazonian tree species suggest that pre-Columbian and colonial-period ecological legacies are associated with modern forest composition.